PENERAPAN KAIDAH FIQHIYYAH DALAM PUTUSAN DISPENSASI NIKAH DI PENGADILAN AGAMA TEMANGGUNG TAHUN 2023 PERSPEKTIF RESPONSIVE LAW THEORY - Zunaeni (JIL : Journal of Indonesian Law, 2025)
This study aims to examine the application of fiqh principles in marriage dispensation decisions at the Temanggung Religious Court in 2023 from the perspective of responsive theory. This study uses a qualitative method with a normative juridical approach, with primary data in the form of marriage dispensation decisions by the Temanggung Religious Court in 2023. Data were collected through literature study, documentation, and interviews with judges, then analyzed through data reduction, data presentation, and conclusion drawing. The results of the study show that of the 291 marriage dispensation cases, there were 111 decisions that were granted with the dominance of three fiqhiyyah rules, namely dar'ul mafasid muqaddam 'ala jalb al-mashalih (8 decisions), idzā ta‘āraḍa ḍararāni fuḍḍila akhaffuhā (103 decisions), and taṣarrufu al-imāmi ‘alā ar-ra‘iyyati manūṭun bil-maṣlaḥah (4 rulings). These findings show that in the perspective of Responsive Law Theory, judges do not only adhere to normative provisions, but also comprehensively consider social, psychological, and readiness aspects of the prospective bride and groom. Thus, the application of fiqhiyyah rules in marriage dispensation rulings reflects the adaptive, contextual, and responsive nature of Islamic law to the realities of society.